Comorbid Conditions in Neonates With Congenital Heart Disease. (August 2016) - Krishnamurthy, Ganga; Ratner, Veniamin; Bacha, Emile; Aspelund, Gudrun
Abstract : Objectives: The objectives of this review are to discuss the pathophysiology, clinical impact and treatment of major noncardiac anomalies, and prematurity in infants with congenital heart disease. Data Source: MEDLINE and PubMed. Conclusion: Mortality risk is significantly higher in patients with congenital heart disease and associated anomalies compared with those in whom the heart defect occurs in isolation. Although most noncardiac structural anomalies do not require surgery in the neonatal period, several require surgery for survival. Management of such infants poses multiple challenges. Premature infants with congenital heart disease face challenges imposed by their immature organ systems, which are susceptible to injury or altered function by congenital heart disease and abnormal circulatory physiology independent of congenital heart disease. For optimal outcomes in premature infants or in infants with multiple congenital anomalies, a collaborative interdisciplinary approach is necessary.